2 - Resources, Poverty and Human Development in Rural Uganda: 10.4314/ad.v25i3.22102 - Bongo, Tenkir (Africa Development, 2000)
Within the current factors and methods of production, Ugandan rural households balance the number of consumers, labourers and the si2e of cultivated holdings. The socially and spatially better-offs, who have more investments in livestock and family labour, enjoy higher levels of land productivity and modest improvement in their per capita income. A quarter of the total income originates from non-agricultural sectors, thereby making these sectors important avenues to poverty reduction even among the rural households.However, expenditure by those above the Poverty Line is equal to expenditure by those below. A large gap exists between the per capita income of the better-off households compared to the poor. When a human development index, including assets, income, social endowments and other positive outcomes of the development process are computed, the differentials narrow down considerably, bringing to the fore the social and economic proximity of the rural households.